Effects of Violence Shown in Media on Children: A Study of Parent’s Perspective - Abid Zafar, Umar Ghazanfar Chaudhary (JECCE, 2023)
Violence mediated programs play a decisive role in cultivating vicious attitudes among children which are damaging the actions of children and their ways of life. This research was designed to investigate the effects of the violent contents shown on media in changing the children’s attitudes. The Researchers applied survey method by quantitatively analyzing the respondent’s views about their children’s habits of watching television and playing video games on computer by using Likert scale for getting an in-depth understanding of behavioral changing which are caused by violent based contents in media. Cultivation theory was applied for recognizing the effects of violent based TV contents on children by using bobo doll experiment. The population of the study was the mothers of those children between 4-12 years from district Gujrat. Total 100 mothers were selected as a sample by using stratified random sampling technique. The strata were made based on the status of women where half of the women were selected as the house wives and half of them were selected as working women. The results of this study show that the aggressive and violent based contents on television and video games have extremely negative effects on the attitudes of the children.